Resting energy expenditure in Japanese athletes - As applied to dietary management for athletes - Taguchi, M.; Oshima, S. (Sports Performance, 2015)
Resting energy expenditure (REE) is known to be influenced by different factors, such as body size, body composition (including mass of internal organs and tissues), thyroid hormones, and menstrual cycle. However, the relationship between these factors and REE has not been fully investigated nor reviewed in a way that is optimally useful for the athletic population. Thus the purpose of the chapter is to introduce and summarize studies which have investigated these relationships in Japanese athletes. Fat-free mass (FFM) constitutes not just skeletal muscle, but also internal organs with high metabolic rates. As FFM becomes larger, these tissues and organs also become larger. Since athletes typically have a large FFM, FFM is the major determinant of REE in athletes and consequently it is strongly recommended that FFM be used to estimate REE for Japanese athletes. The daily energy requirement can be estimated based on the REE, and therefore REE is an important part of a sound dietary management program for maximizing athletic performance. Nevertheless, further studies are necessary to investigate such poorly understood factors as genetic background and brown adipose tissue, as well as how these and other elements influence the REE of Japanese athletes.